2006
DOI: 10.1530/eje.1.02206
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the metabolic syndrome in obese Spanish pediatric population

Abstract: Objective: Obesity is associated with insulin-resistance (IR), type 2 diabetes (T2D) and a constellation of cardiovascular risk factors at the early years of life. These features define the so-called metabolic syndrome (MS). Aims: To assess the frequency of the MS among obese pediatric Spanish population and analyse the individual contribution and the predictive potential of individual components to the development of the syndrome. Patients and methods: A total of 429 patients, 220 boys and 209 girls, aged 4-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
0
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 48 publications
10
31
0
15
Order By: Relevance
“…The comparison of these results with those described by other authors reveals that the prevalence found is similar than references from Cook (28.7%) [18], Cruz (30%) [22], Weiss (38.7%) [23] Viner (30%) [24] and Ferranti (31.2%) [25] in obese UK or American children and adolescents, although slightly higher than references from Olza (16.8%) [13], Lopez-Capapé (18%) [26] and Tapia (18.6%) [27] in Spanish obese pediatric population. Nevertheless, the contrast of the rate of prevalence from different Studies has a relative value, since the criteria applied are different, and even different cut points for each component of MS are used [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The comparison of these results with those described by other authors reveals that the prevalence found is similar than references from Cook (28.7%) [18], Cruz (30%) [22], Weiss (38.7%) [23] Viner (30%) [24] and Ferranti (31.2%) [25] in obese UK or American children and adolescents, although slightly higher than references from Olza (16.8%) [13], Lopez-Capapé (18%) [26] and Tapia (18.6%) [27] in Spanish obese pediatric population. Nevertheless, the contrast of the rate of prevalence from different Studies has a relative value, since the criteria applied are different, and even different cut points for each component of MS are used [28].…”
Section: Discussionsupporting
confidence: 82%
“…This syndrome is characterized by a cluster of symptoms associated to obesity, such as insulin resistance, arterial hypertension and dyslipidemia, and its interest lies in the high predictive value for cardiovascular disease and type 2 diabetes in adulthood, especially when it is already present in school children and/or adolescents [5][6][7][8][9]. Even when the International Diabetes Federation (IDF) [10] refers to the inability for diagnosis in school age, epidemiological data allow suspecting that metabolic syndrome or its components are already present at early stages [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the prevalence of MES in normal-weight adolescents was found to be less than 1% [20]. Studies conducted on prevalence of MES in obese children indicate varied numbers in European countries (in France 15.9%, in Italy 13.9%, in Spain 18%) [21][22][23]]. Weiss's study, examining the correlation between obesity grades and the prevalence of MES, states a prevalence of 38.7% in moderate obese adolescents (VKI z score 2-2.5) and a prevalence of 49.7% in severely obese adolescents (VKI z score >2.5) [24].…”
Section: Discussionmentioning
confidence: 98%
“…12 Nonetheless, the three proposed definitions have been used in several studies carried out in pediatric populations, which reported high-prevalence of the MS in obese children and adolescents. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results of these studies varied according to the selected diagnostic criteria used, as established by a recent comparison study. 34 Moreover, in an evaluation of the different prevalence yields using different definition, Goodman et al 35 found that ATP III definition identified half as many children and adolescents as having MS as did WHO definition in the same population.…”
Section: Introductionmentioning
confidence: 99%